De la crise a une croissance nouvelle : Extraits de discours de Michel Camdessus. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
Extraits de discours de Michel Camdessus.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Foreign Exchange; Informal Economy; Underground Econom